STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT BELAJAR SISWA MELALUI PEMBELAJARAN ONLINE (DARING) KELAS XI OTOMATISASI DAN TATA KELOLA PERKANTORAN DI SEKOLAH SEKOLAH MENENGAH KEJURUAN ARDJUNA 01 MALANG - Fatika Amalia Asri; Muhammad Hanief; Atika Zuhrotus Sufiyana (VICRATINA, 2020)
Learning strategies are general learning that will be taken and used by teachers to choose some learning methods that are appropriate in learning. Choosing and using learning strategies is also very important. So that learning can run well. This research is focused on the interest in learning PAI students of class XI-OTKP, PAI teacher strategy in increasing the interest in learning of students of class XI-OTKP, which is beneficial for teachers in learning material for class XI-OTKP pies at SMK Ardjuna 01 Malang through online  learning. This study aims to describe the interest in learning PAI students of class XI-OTKP, describe the strategies of PAI teachers in increasing the interest in learning of students of class XI-OTKP, describing the themes studied by the PST teachers at SMK Ardjuna 01 Malang through online  learning. This type of research is a case study research. Data collection techniques used are, unstructured observation, semi-structured interviews, and documentation on PAI subject teachers, curriculum waka and a number of XI-OTKP students in SMK Ardjuna 01 Malang. In the data analysis activity there are four steps namely, collecting data, reducing data, presenting data and gathering conclusions.